Giant Coronary Artery Aneurysm Causing Acute Anterior Myocardial Infarction. (6th November 2016) - Yanık, Ahmet; Arslan, Uğur; Akçay, Murat; Menekşe, Serdar; Yazgan, Uğur Gökmen
Abstract : A 70-year-old man with hypertension was admitted to our coronary ICU with acute anterior MI. Emergent primary PCI was planned and coronary angiography was performed. LAD artery was totally occluded in the proximal segment just after a huge 32 × 26 mm sized aneurysm. Emergent CABG operation was performed in 75 minutes because of multivessel disease including the RCA and left circumflex artery. Aneurysm was ligated and coronary bypass was performed using LIMA and saphenous grafts. The postoperative course of the patient was uneventful. He was discharged with medical therapy including ASA, clopidogrel, and atorvastatin. He was asymptomatic at his polyclinic visit in the first month.